Духовні засади сучасного кримінально-правового впливу в українській класичній літературі - Козаченко, Олександр Васильович; Козаченко, Александр Васильевич; Kozachenko, Aleksandr (My University, 2013)
On the basis of the offered cultural-anthropological approach samples of Ukrainian classical literature are researched to establish relations between society and applied criminally-legal measures of influence on the people who have committed a crime. Indissoluble relation between state criminally-legal policy of counteraction of criminality and the culture of Ukrainian people is highlighted.
Козаченко О. В. Духовні засади сучасного кримінально-правового впливу в українській класичній літературі / О. В. Козаченко // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 342-351.
Keywords: кримінальне право; культурно-антропологічний вимір; гуманізація; українська класична література; кримінально-правові заходи; уголовное право; культурно-антропологическое измерение; гуманизация; украинская классическая литература; уголовно-правовые меры; criminal law; cultural-anthropological measurement; humanization; Ukrainian classical literature; criminally-legal measures